Reconstruction of Differentiation-Based Islamic Religious Education Learning Strategies to Accommodate Cognitive and Social Diversity - Mohammad Zakiyuddin; Muhlisin; Rahmi Anekasari (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to reconstruct a differentiation-based Islamic Religious Education (PAI) learning strategy to accommodate the cognitive and social diversity of students. The background of this research is based on the fact that PAI learning practices still tend to be uniform, while classroom conditions show a high level of heterogeneity. The approach used in this study is qualitative with a conceptual study through an analysis of relevant literature from the past five years. The results of the study indicate that differentiated learning can be a strategic solution through the development of three main aspects: content differentiation, process differentiation, and learning products. In addition, the implementation of this strategy is supported by the use of diagnostic assessments, flexible grouping, and adaptive adjustments to learning methods and media. The reconstruction of the PAI learning strategy also emphasizes the importance of integrating Islamic values in every learning process, thus not only improving cognitive learning outcomes but also strengthening the affective and spiritual dimensions of students. The role of the teacher as an adaptive facilitator is a key factor in the successful implementation of differentiated learning. Thus, this study concludes that a differentiation-based learning strategy can create PAI learning that is more inclusive, contextual, and oriented to the needs of students, and contributes to improving the overall quality of learning.